Endodontic Management of a Maxillary First Molar with Two Palatal Canals and a Single Buccal Canal: A Case Report - Leila Atash biz Yeganeh; Mamak Adel; Reza Vahedi; Maryam Tofangchiha (Case Reports in Dentistry)
Thorough knowledge of root canal morphology is essential for the endodontic therapy. There are rare variations in canal number and configuration in maxillary molars, which could affect treatment outcome. This paper presents the endodontic management of a maxillary first molar with two palatal canals in one root (Vertucci type IV) and a single buccal canal. In this paper cone-beam computed tomography was made to asses this morphology. This paper is intended to reinforce clinician’s awareness of the rare morphology of root canals.